Circuit Models for Interconnects Using 3D Computational Techniques - Essakhi, B.; Benel, J.; Smail, M.; Pichon, L.; Akoun, G. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a method to generate circuit models from 3D distributed structures. In the first step a broadband characterization of the device is obtained through a reduced order modeling technique. Then in the second step a rational approximation of the coefficients of the impedance matrix is derived using a root mean squared procedure. An equivalent circuit is then synthesized and allows a global circuit simulation of the whole structure. The proposed methodology can be used with a segmentation technique for the analysis of complex structures: a whole 3D structure can be subdivided into smaller parts. Each part is characterized by an equivalent circuit deduced from wideband analysis. The connection between the substructures makes available a global simulation of the whole system inside a circuit platform (SPICE for example). Numerical results are shown for different kinds of interconnects (tracks and cables).